Outcomes of Pediatric Central Nervous System Tuberculosis in California, 1993–2011. (4th September 2018) - Duque-Silva, Alexandra; Hampole, Varsha; Cheng, Yi-Ning; Flood, Jennifer; Barry, Pennan M
Abstract: Background: Our goal was to describe the characteristics and posttreatment outcomes of pediatric patients with central nervous system (CNS) tuberculosis (TB) and to identify factors associated with poor outcome. Methods: We included children aged 0 to 18 years with CNS TB reported to the California TB registry between 1993 and 2011. Demographics, clinical characteristics, severity of disease at presentation (Modified Medical Research Council stage I, II, or III [III is most severe]), treatment, and outcomes during the year after treatment completion were abstracted systematically from the medical and public health records. Patient outcomes were categorized as good or poor on the basis of disability in hearing, vision, language, ambulation, and development and other neurologic deficits. Results: Among 151 pediatric CNS TB cases reported between 1993 and 2011 in California for which records were available, 92 (61%) cases included sufficient information to determine outcome. Overall, 55 (60%) children had a poor outcome. After we adjusted for age (0 to 4 years), children with stage III severity (vs I or II; prevalence rate ratio [PRR], 1.4 [95% confidence interval (CI), 1.1–1.9]), a protein concentration of >100 mg/dL on initial lumbar puncture (PRR, 1.2 [95% CI, 1.03–1.4]), or infarct on neuroimaging (PRR, 1.2 [95% CI, 1.04–1.3]) were at increased risk for a poor outcome. In multivariate analysis, an age of 0 to 4 years (vs >4 years; PRR, 1.4 [95% CI, 1.2–1.7]) and a stage II or III Modified Medical Research Council score (vs stage I; PRR, 1.2 [95% CI, 1.03–1.5]) remained significantly associated with poor outcome. Conclusions: Pediatric patients with CNS TB in California are left with high rates of disabling clinical sequelae after treatment. The identification of modifiable factors is critical for improving outcomes. Abstract : During our study period, the majority of children with central nervous system tuberculosis in California had a poor outcome. Young age and severity of disease at presentation were associated with poor outcome. Modifiable factors for improving outcomes should continue to be sought.